Study on shipyard location and model development - Thaib Rizwan; Husaini Husaini; Husni Husin; Akhyar Akhyar (Depik, 2022)
The shipyard location and model highly influence shipyard industry development. This study aims to assess the location feasibility and determine the shipyard model suitable for shipyard industry development in Kutaraja Fishing Port. The study was conducted in Kutaraja Fishing Port. AHP method was used to determine the location and model, then analyzed using theExpert Choice v11software. The data were collected using questionnaire interviews and further allocated the value using paired comparison scale table. The result shows that the shipyard industry is feasible to be developed in an area where land parameters adjacent to the waters have a maximum value of 37.3% compared with the five other parameters. The suitable shipyard model to be developed in Kutaraja Fishing Port is the slipway type with a value of 46.1%.Keywords:LocationModelShipyard